Effect of circuit bodyweight training on health-related physical fitness in sports college students: a quasi-experimental study - Sutoro Sutoro; Dewi Nurhidayah; Astini Asri; Ansar CS; Pinton Setya Mustafa (Sriwijaya Journal of Sport, 2026)
Research Problems: Physical fitness is a fundamental component of health and athletic performance among physical education students. However, limited access to training equipment and facilities often restricts the implementation of effective resistance training programs. Bodyweight training has emerged as a practical and cost-effective alternative, yet empirical evidence regarding its effectiveness in improving multiple components of physical fitness among sports college students remains limited. Research Objectives: This study aimed to examine the effect of a circuit bodyweight training program on the physical fitness of sports college students by comparing changes in fitness outcomes between an experimental group and a control group. Methods: This study employed a quasi-experimental design using a two-group pre-test–post-test approach. A total of 43 sports college students were randomly assigned to an experimental group (n = 22) and a control group (n = 21). The experimental group completed a circuit bodyweight training program consisting of eight exercises over 16 training sessions, while the control group followed regular physical activity. Physical fitness was assessed using a battery of tests, including body mass index (BMI), sit-and-reach, leg and back dynamometer, and the Cooper test. Data were analysed using descriptive statistics and analysis of covariance (ANCOVA) with JASP statistical software. Results: The ANCOVA results demonstrated statistically significant differences between the experimental and control groups following the intervention (p < .05). Participants who completed the circuit bodyweight training program showed greater improvements in overall physical fitness compared with those in the control group. These findings indicate that a structured bodyweight training program can effectively enhance physical fitness among sports college students. Conclusion: Circuit bodyweight training conducted over 16 sessions is an effective and economical approach for improving physical fitness in sports college students. The findings support the use of bodyweight exercises as an accessible resistance training strategy in physical education and sports settings, particularly where training facilities are limited. This study contributes to the growing evidence on low-cost exercise interventions and provides practical guidance for educators and coaches. Future studies should compare bodyweight training with other resistance training methods, such as multiple-set or free-weight training, over longer intervention periods and across different populations.